ESPAÑOL - García, Jorge (2020)
This research proposes a Wetland Index (IB) to identify wetlands, located above 3800 meters above sea level. The IB proposal is a summary of Garcia Dulanto's master thesis (2018) and is based on two methods: the first based on the Linear Spectral Unmixing classication that uses spectral signatures selected from characteristic elements of the study area. Spectrally ideal signatures (endmember, EM) were selected to represent: wetlands (wetland EM), rocks (rock EM) and bare soil (soil EM). The second method is based on the biophysical indices or parameters NDVI, NDWI and NDII. The RGB image combination: NDII, NDVI, NDWI shows the wetlands in the study area in yellow tones. The two methods are integrated using Pearson's correlation between the fraction of the endmember-bofedal and those of the bofedales. Maximum and minimum correlation is obtained with the NDWI and NDII indices. With these indices, an index IB = (NDWI - NDII) / (NDWI + NDII) is proposed to directly zone the wetlands. The IB was validated by means of the high resolution images of the Google Earth Pro software, obtaining a 98.36% accuracy.